Diffusion of Application Policy Innovation Pekan Kita (PEKA) in Pekanbaru City - Eko Handrian; Umi Muslikhah; Rosmita Rosmita (Jurnal Administrasi Publik, 2024)
Policy Innovation in the field of digitalization in various government sectors has become like a trend, digitalization is not only limited to providing technology, good governance will create sustainable digitalization technology to support the acceleration of sustainable development goals. The Pekan Kita Application (PEKA) as one of the Innovations of the Pekanbaru City Information, Statistics and Coding Communication Service was launched under conditions of non-integration and overlapping functions. This research aims to understand the diffusion of digitalization technology policy innovations in government. This research uses qualitative methods by collecting interview data, observation and documentation as well as data analysis, data presentation, reduction and drawing conclusions. The results show that the diffusion of the Pekan Kita application policy is the result of learning, competition, imitation and coercion mechanisms that are not carried out comprehensively resulting in failure and innovation limited to providing technology that is not adopted by all stakeholders. This research is expected to become a reference in the diffusion of policy innovations that involve integration processes.